Obesity Is Not Associated with Increased Operative Complications in Single-Site Robotic Partial Nephrectomy - Komninos, Christos (Yonsei Med J, 2015)
PURPOSE: To evaluate the impact of high body mass index (BMI) on outcomes following robotic laparoendoscopic single-site surgery (R-LESS) robotic-assisted laparoscopic partial nephrectomy (RPN). MATERIALS AND METHODS: Data from 83 Korean patients who had undergone robotic partial nephrectomy from 2006 to 2014 were retrospectively analyzed. The subjects were stratified into two groups according to WHO definitions for the Asian population, consisting of 56 normal range (BMI=18.5-24.99 kg/m(2)) and 27 obese (≥25 kg/m(2)) patients. Outcome measurements included Trifecta achievement and the perioperative and postoperative comparison between high and normal BMI series. The measurements were estimated and analyzed with SPSS version 17. RESULTS: Tumor's complexity characteristics (R.E.N.A.L. score, tumor size) of both groups were similar. No significant differences existed between the two groups with regard to operative time (p=0.27), warm ischemia time (p=0.35) estimated blood loss (p=0.42), transfusion rate (p=0.48) renal function following up for 1 year, positive margins (p=0.24) and postoperative complication rate (p=0.34). Trifecta was achieved in 5 (18.5%) obese and 19 (33.9%) normal weight patients, respectively (p=0.14). In multivariable analysis, only tumor size was significantly correlated with the possibility of Trifecta accomplishment. CONCLUSION: Our findings suggest that R-LESS RPN can be effectively and safely performed in patients with increased BMI, since Trifecta rate, and perioperative and postoperative outcomes are not significantly different in comparison to normal weight subjects.